INVESTIGATION OF THE PROCESS OF EXTRACTION OF TARGET COMPONENTS FROM HOPPER RAW MATERIALS - Запорожец, Юлия; Бродяга, Татьяна (SWorldJournal, 2021)
Hop growing is an important branch of agricultural production, the products of which have many applications, from brewing to cosmetology.For a long time, Ukraine ranked 5th in the world after the United States, Germany, China and Czechoslovakia in the c